Pre-Competitive Anxiety: A comparative study between “Under 12” and Senior teams in football (Ansiedad Pre-Competitiva: Estudio comparativo entre equipos de fútbol infantil y fútbol senior) - João Serrano; Rui Reis; Teresa Fonseca; Rui Paulo; Samuel Honório; Marco Batista (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The present investigation intends to study if the importance and the difficulty of the game, the pre-competitive anxiety (somatic and cognitive) and the levels of self-confidence in football were influenced by the competitive level (Under 12 and Seniors) and also where the game took place (home / outside) and to verify the correlations between these variables. The sample was intentional and consisted of 85 male athletes, participants in the regional championship of “Under 12” and Seniors. The “Under 12” athletes (35) were aged between 11 and 12 years (M = 11.02 ± 0.37) and the Senior athletes (50) were aged between 18 and 35 years (M = 26.66 ± 4.41). The instrument used was the Competitive State Anxiety Inventory (CSAI-2) of Martens et al. (1990) and translated and validated into Portuguese language by Raposo & Fernandes (2004). The results showed that, regardless of the competitive level (Under 12 and Seniors), athletes showed high levels of importance and difficulty to games performed both at home and away from home. Game importance and difficulty levels as well as levels of cognitive and somatic anxiety were higher in the “Under 12” teams, while self-confidence levels were higher in Senior teams. Positive correlations were found between the importance and difficulty of the games, between cognitive anxiety and somatic anxiety. But, the negative correlations were found between cognitive and somatic anxiety and self-confidence.